Computerized cognitive stimulation for people with dementia or with mild cognitive impairment: a bibliometric review - Sobral, Sónia Rolland (Dement Neuropsychol, 2021)
Many studies have found that non-pharmacological interventions, such as cognitive stimulation (CS), can benefit people with dementia (PWD) or with mild cognitive impairment (MCI). The use of the computerized cognitive stimulation (CCS) had proven to be an ally to those who want to detect and mitigate this disease. OBJECTIVE: The purpose of this paper was to analyze the scientific production in CCS in PWD or with MCI in journals indexed in Clarivate Analytics’ Web of Science and Elsevier’s Scopus since 2000. METHODS: Data collected from Web of Science and Scopus during 2000–2019. RESULTS: The data show that dementia research is exponentially developing following the evolution of widespread use of computer science. As such, this article was of enormous importance doing a bibliometric analysis of what has been done in the area since the beginning of this century. The search terms identified 61 papers related to the use of computers applied to CS in PWD or MCI, and the International Journal of Geriatric Psychiatry and Journal of Alzheimer’s Disease had the largest number of publications. The most cited article was the Faucounau et colleagues. Major research’ countries are United Kingdom, Spain and United States. CONCLUSIONS: The findings in these papers were analysed to find recommendations for future work in this area. The CCS has been increasingly used as an intervention tool for PWD or MCI, and there still seems to be a possibility for evolution in good quality publications.